ICT and social media digital initiatives for effective dissemination of Soybean technologies: ICT and social media digital initiatives for effective dissemination of Soybean technologies - B U DUPARE; SAVITA KOLHE (Journal of Oilseeds Research, 2023)
In India, the use of social media and ICTs has gained popularity in the last decade consequent to the digital revolution. In line with these developments, the ICAR-Indian Institute of Soybean Research has started use of social media platforms like WhatsApp, YouTube and Facebook etc. for dissemination of information related to the improved soybean production technologies developed by the Soybean R&D system and facilitating feedback mechanisms among the clients and their interaction with the research system using different ICT tools. Institute has also developed many software to use the potential of Information Communication Technologies (ICT) in best manner. These ICT tools help the farming as well as scientific community in solving different problems and improve and issues as well as for decision making in real time situations.